High Incidence of Asymptomatic Phase I IgG Seroconversion After an Acute Q Fever Episode: Implications for Chronic Q Fever Diagnosis. (23rd September 2021) - Rodríguez-Fernández, Miguel; Espíndola Gómez, Reinaldo; Trigo-Rodríguez, Marta; Castro, Carmen; Martínez Pérez-Crespo, Pedro; Herrero, Rocío; León, Eva M; Bernal, Samuel; Corzo, Juan E; Merchante, Nicolás
Abstract: Background: The aim of this study was to describe the natural history of acute Q fever, including its clinical and serological evolution and progression to chronic Q fever. Methods: Observational cohort study (January 2011–September 2020) performed at Valme University Hospital (Seville, Spain). Inclusion criteria: (1) patients aged ≥18 years; (2) acute Q fever diagnosis, defined as suggestive symptoms in the presence of phase II immunoglobulin G (IgG) titer >1:256; (3) at least 6 months' follow-up after the acute Q fever episode. The incidence of seroconversion to a chronic Q fever serological pattern, defined as phase I IgG titers ≥1:1024 6 months after acute Q fever diagnosis, was assessed. Results: During the study period, 117 patients were included. Thirty-four (29%) patients showed phase I IgG titers ≥1:1024 6 months after acute Q fever diagnosis. All patients with classic serological criteria for chronic Q fever diagnosis remained asymptomatic despite no specific treatment, with a median (quartile 1–quartile 3 [Q1–Q3]) follow-up of 26.5 (14–44) months in this subgroup. No cases of Q fever endocarditis nor other persistent focalized infection forms were observed during the study period. Conclusions: A significant proportion of acute Q fever patients develop classic serological criteria for chronic Q fever diagnosis in the absence of additional data of chronic Q fever. Consequently, phase I IgG cutoff titers >1:800 should not be used as a criterion to consider such a diagnosis. The incidence of persistent focalized infection forms after acute Q fever is extremely low and does not justify the use of prophylaxis strategies. Abstract : Thirty-four of 117 acute Q fever patients developed classic serological criteria for chronic Q fever diagnosis without other data of such a diagnosis. Consequently, phase I IgG titers >1:800 should not be used as a chronic Q fever diagnosis criterion.